Atrial fibrillation prevalence and management patterns in a Middle Eastern community in the United States: A retrospective study - Mohamad Raad; Christopher Lewis; Mohamed Ramzi Almajed; Tarek Makki; Marwan Refaat; Arfaat Khan; Marc Lahiri (American Heart Journal Plus, 2022)
Atrial fibrillation (AF) is the most common sustained cardiac dysrhythmia in the United States, and its prevalence is expected to increase along with associated morbidity and economic burden. Prior research has demonstrated differing prevalence patterns of AF between racial and ethnic groups, with lower rates identified in Black patients. However, to date there have been no studies on AF prevalence in people of Middle Eastern descent within the United States. This retrospective cross-sectional study aimed to characterize prevalence patterns of AF in Middle Eastern patients in Southeast Michigan relative to White and Black patients. The final cohort included 919,454 patients with a median (IQR) age of 53 (33) years (515,902 [56 %] female). The overall prevalence of AF was approximately 5 %. We observed a lower prevalence of AF in Middle Eastern (2.8 %) and Black patients (3.4 %) than in White patients (6.5 %). Middle Eastern patients with AF were younger with a lower prevalence of cardiovascular risk factors than White patients. Multivariable analysis showed that Middle Eastern (OR 0.75; 95 % CI 0.71–0.80; P < 0.001) and Black racial identity (OR 0.48; 95 % CI 9.47–0.49; P < 0.001) were associated with a lower odds of AF, even after adjustment for traditional risk factors.